Physical Condition Profile of West Java Finswimming Athletes at the Aceh National Sports Week (PON) Based on Competition Number - Raqiel Az-zahra; Yati Ruhayati; Tian Kurniawan (Universitas Negeri Semarang, 2026)
This research is motivated by the importance of mapping physical conditions as a basis for developing specific training programs for finswimming athletes, especially for national-level competitions such as the National Sport Week. The purpose of this study was to determine the physical condition profile of West Java finswimming athletes based on the competition events at the 2024 Aceh PON. The method used was descriptive quantitative with a total of 14 athletes (n=14) as subjects. Data collection was carried out through a series of physical condition tests covering flexibility, reaction speed, power, endurance, core stability, and VO2Max. Data analysis used descriptive statistics in the form of means, standard deviations, and percentages. The results showed that the core stability component had optimal achievement (100%) in all events, while leg power was the weakest component with an average of around 24%. In addition, aerobic capacity (VO2Max) showed variation between events, with a range of 76% to 99%, where middle to long distance events tended to have higher values than sprints. The conclusion of this study confirms that although athletes' core stability is already very good, increasing leg power needs to be a top priority in the training program. In addition, the differences in VO2Max profiles between events indicate the need for a more specific training approach according to the demands of each event.